Methodology of ECG Interpretation in the Louvain Program - Brohet, C. R.; Derwael, C.; Robert, A.; Fesler, R. (Methods of Information in Medicine, 1990)
The Louvain program performs the analysis and interpretation of the vectorcardiogram (VCG) to increase the clinical utility of ECG analysis. Among its original features, there are (1) a high-resolution vector-loop display for visual analysis, (2) quantitative analysis of the spatial VCG using age-sex stratified limits, (3) separate software for adult and pediatric series and (4) complementary deterministic and statistical methods of diagnostic classification. Using objective, ECG-independent evidence as a reference standard, the Louvain program has shown satisfactory levels of diagnostic accuracy in most basic categories. However, its usefulness is especially marked in “borderline” or “complex” situations, where the 12-lead ECG cannot provide a clear answer. It corresponds to the concept of “computer-assisted ECG interpretation” as opposed to “computer ECG analysis”.
Keywords: VCG Analysis; Computerized Vectorcardiography